2015
DOI: 10.1139/cgj-2014-0157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of consolidation on responses of a single pile subjected to lateral soil movement

Abstract: Given extensive research carried out to study pile response subjected to lateral soil movement in clay, the effect of consolidation on the pile–soil interaction is rarely considered and systematically investigated. For this reason, four centrifuge tests were conducted to simulate construction of embankment adjacent to existing single piles in soft clay, considering two typical drainage conditions (i.e., drained and undrained conditions) and two typical pile lengths (i.e., relatively long pile and short pile). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this hypothesised study, the parameters for silty clay were adopted Mašín et al, [9]. All the model parameters for silty clay reported by Wang et al, [25] are summarised in Table 1. The coefficient of lateral earth pressure at rest, Ko is estimated by Mayne and Kulhawy's [24] equation Ko=(1-sinφ)(OCR) sinφ .…”
Section: Constitutive Modelmentioning
confidence: 99%
“…In this hypothesised study, the parameters for silty clay were adopted Mašín et al, [9]. All the model parameters for silty clay reported by Wang et al, [25] are summarised in Table 1. The coefficient of lateral earth pressure at rest, Ko is estimated by Mayne and Kulhawy's [24] equation Ko=(1-sinφ)(OCR) sinφ .…”
Section: Constitutive Modelmentioning
confidence: 99%
“…In this hypothesised study, the parameters for silty clay were adopted Mašín et al, [21]. All the model parameters for silty clay reported by Wang et al, [24] are summarised in Table 1. The coefficient of lateral earth pressure at rest, Ko is estimated by Mayne and Kulhawy's [25] equation Ko=(1-sinφ)(OCR) sinφ .…”
Section: Constitutive Modelmentioning
confidence: 99%
“…This problem is considered to be caused by the inclination of the pile under the lateral pressure of the soil layer under an adjacent surcharge load 5 . Previous studies of this issue, have included the field measurements 2 , 6 9 , centrifuge tests 10 12 , and numerical analyses 13 18 . These studies revealed that the lateral offset on the pile was caused by the adjacent unilateral surcharge, which resulted in the deflection of the superstructure such as bridge girders and high-rise buildings 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al 22 presented an investigation on the short- and long-term passive loading on the piles using the two dimensional elastoplastic-consolidation coupled FE analyses with large strain mode, and the results showed that passive pile loading was primarily affected by the magnitude of the surcharge load and degree of consolidation. Wang et al 12 performed four centrifuge model tests and numerical analyses to study the response of single pile subjected to lateral soil movement, and the results showed that it was necessary to consider the effect of consolidation on the pile-soil interaction. Li et al 23 conducted a series of field tests to examine the behavior of piles in the foundation with deep soft soils subjected to adjacent surcharge load, and a 3D FE model was established to study the factors affecting the consolidation of the soft soil.…”
Section: Introductionmentioning
confidence: 99%